Niveles de hormona antimülleriana y factor neurotrófico derivado del cerebro como predictores de función ovárica - Carvajal G., Rodrigo; Alba S., Juan F.; Cortínez C., Armando; Carvajal M., Antonio; Miranda V., Cristián; Romero O., Carmen; Vantman B., David (Revista Hospital Clínico Universidad de Chile, 2012)
Infertility is now recognized as a disease by World Health Organization. It affects up to 15% of couples of childbearing age and un 4-8% of them will require high complexity assisted reproduction techniques. The delay of childbearing age involves the submission of the reproductive lifetime of the ovary. Determination of the ovarian reserve would save time and optimize resources for family planning. Antimulleriana hormone (AMH) is a marker of ovarian reserve, both quantitatively and qualitatively. It can be used in the research of premature ovarian failure, polycystic ovary syndrome (PCOS), menopause, as well as ovarian hyperstimulation syndrome (OHSS) and in vitro fertilization (IVF) poor responder patients. Brain derived neurotrophic factor (BDNF), member of growth factors family Neurotrophins, is produced by the granulosa cells and it is directly involved in the quality and timing of oocyte maturation. This review describes the reasons why the measurements of AMH and BDNF would be useful to predict the reproductive outcomes of patients undergoing IVF treatments